PENGARUH KOMPOS DAUN GAMAL TERHADAP PERTUMBUHAN DAN HASIL BEBERAPA VARIETAS PADI SAWAH - I Komang Ardiasa; Ismail Djamaluddin; Nurmasyitah Mambuhu (Fakultas Pertanian Universitas Tompotika Luwuk, 2023)
Gamal leaf compost is the result of the process of decomposing organic matter that is decomposed by microorganisms that can produce nutrients needed by plants. The use of compost can also reduce and compensate for the continuous use of chemical fertilizers by farmers. The selection of high-yielding varieties is also the most important thing in increasing rice yields. This study aims to determine the effect of gamal leaf compost on the growth and yield of several rice varieties. The research was conducted on rice fields in Karya Makmur Village, West Toili District, Banggai from July to November 2021. This study used a randomized group design consisting of 2 treatment factors. The first factor in giving gamal leaf compost consists of 4 levels, namely P0 = 0 kg / plot as the ruler, P1 = 0.8 kg / plot, P2 = 1.6 kg / plot, P3 = 2.4 kg / plot. The second factor of using varieties consists of 3 levels, namely V1 = Ciherang, V2 = Cisantana, V3 = Sintanur. The results of fingerprint analysis showed that gamal leaf compost treatment had a real and very real effect on the growth and yield of rice fields, while the use of varieties had a real and very real effect on growth and had no effect on rice field yields. The interaction between the two treatments had a significant effect on plant height of 3-4 MST. The best dose for plant height parameters, number of productive tillers, panicle length, grain weight per plot with a dose of gamal leaf compost with a dose of 2.4 kg / plot, while in P2 treatment with a dose of 1.6 kg / plot gamal leaf compost is the best dose on the parameters of the number of tillers.